PENGARUH PEMBIASAAN SHALAT BERJAMAAH TERHADAP KEAKTIFAN SISWA BELAJAR DI SDIT AMSAR KOTA BARU KARAWANG - Hilman Fakhrulian Zahab, Muhammad; Widiawati, Diah; Febiani Musyadad, Vina (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study addresses the problem of investigating the extent to which congregational prayer impacts students’ learning activities. Although at SDIT Amsar the mplementation of congregational prayer has been systematically organized, students’ learning activeness has not yet demonstrated positive outcomes.This study aims to determine the effect of habitual congregational prayer on student learning activeness at SDIT AMSAR Kota Baru Karawang. The research method used was quantitative with a correlational approach. The research sample consisted of 50 students from grades IV, V, and VI selected through purposive sampling. The instrument used was a closed questionnaire with a Likert scale. The results showed a significant positive effect between habitual congregational prayer and student learning activeness. The correlation coefficient obtained was 0.722 with a significance level of 0.000 (<0.05), indicating a strong relationship between the two variables. The conclusion of this study is that consistent congregational prayer habits at school can improve students' learning activeness, both physically and mentally. It is recommended that schools continue to optimize this habit as an integral part of character education.